1995
DOI: 10.1093/treephys/15.9.611
|View full text |Cite
|
Sign up to set email alerts
|

Water deficits at anthesis reduce CO2 assimilation and yield of lychee (Litchi chinensis Sonn.) trees

Abstract: Ten-year-old 'Tai So' lychee (Litchi chinensis Sonn.) trees growing on a sandy loam soil in subtropical South Africa (latitude 25 degrees S) were watered weekly (well-watered treatment) or droughted from late July until January (drought treatment). After 16 weeks, at which time the trees obtained most of their water from below 150 cm, average soil water content at 0 to 150 cm depth was 14.5 +/- 0.1% in the well-watered treatment and reached a minimum of 7.6% in the drought treatment. At Week 7, minimum leaf wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 7 publications
1
13
0
1
Order By: Relevance
“…Finally, further possible K c values are computable if the variability of the K e,max value is additionally accounted for. Hence, the results are in accordance with Menzel et al (1995), who reported a K c value range between 0.4 and 1.2. The suggested K c value of Bredell (1971) (K c =0.85) would mean a K cb of 0.8 (for dry soil surfaces with K e =0.05) and ties in with the recommendation in this study to set K cb equal to 0.8.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, further possible K c values are computable if the variability of the K e,max value is additionally accounted for. Hence, the results are in accordance with Menzel et al (1995), who reported a K c value range between 0.4 and 1.2. The suggested K c value of Bredell (1971) (K c =0.85) would mean a K cb of 0.8 (for dry soil surfaces with K e =0.05) and ties in with the recommendation in this study to set K cb equal to 0.8.…”
Section: Discussionsupporting
confidence: 92%
“…Root distribution of lychee trees has only been reported in acid soils of a subtropical region (Menzel et al, 1990). Bredell (1971) suggested using a general crop coefficient (K c ) to calculate the potential evapotranspiration (ET pot ) of lychee trees whereas Menzel et al (1995) published a K c value range. Finally, no data was found on lychee tree interception and evaporation underneath the tree canopies.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, experiments in India, Africa and Australia indicated that periods of drought can have different effects on yield, quality and cracking depending on the level and period of water deficit. In South África, a water deficit during fruit development increased the number of cracked or rippened fruits (41%) in relation to fruits harvested from trees with good irrigation (10%) (Menzel et al, 1995). Abbott et al (1986) showed reduction of cracking problems in tomato fruits, by increasing irrigation frequencies.…”
Section: Evaluación De Factores Climáticos En La Incidencia De Frutosmentioning
confidence: 99%
“…Al respecto, experimentos en la India, África y Australia indicaron que periodos de sequía pueden tener diferentes efectos en el rendimiento, calidad y bretado dependiendo del nivel y periodo de déficit hídrico. En Sudáfrica, un déficit hídrico durante el desarrollo del fruto incrementó la cantidad de frutos rajados o bretados (41%) en relación a frutos cosechados de árboles con buen riego (10%) (Menzel et al, 1995). Abbott et al (1986) reportaron reducción de problemas de bretado en frutos de tomate, mediante el incremento de frecuencias riego.…”
Section: Evaluación De Factores Climáticos En La Incidencia De Frutosunclassified
“…In a related experiment in South Africa, water was withheld from trees from just before emergence of the inflorescences until four weeks after harvest (Menzel et al ., 1995). Water deficits reduced initial fruit set from 21.0±1.1fruit in an inflorescence to 14.1±1.8 fruit, and also the final set at harvest from 7.0±0.3 to 2.0±0.5 fruit.…”
Section: Water Prodctivitymentioning
confidence: 99%